A Comparative Study of the Food and Feeding Habits of Chrysichthys nigrodigitatus and Brycinus nurse in a Tropical River (Biological Sciences - PJSIR, 2005)
A comparative study of food and feeding habits of two fish species, Chrysichthys nigrodigitatus (Lacepede) and Brycinus nurse (Ruppel) was carried out in the Ethiope, a tropical river. Fish species were procured from fishermen, using cast-nets, fish traps, hooks and lines for fish catch. Specimens were chilled with ice-blocks in a heat-insulated cooler and transported to the laboratory at the University of Benin for analysis. One hundred fish specimens were examined and their stomach contents analysed. Two methods were applied for the analysis, namely, the frequency of occurrence method and the volumetric method. The result of the analysis showed that C. nigrodigitatus was an omnivorous detritivore, while• nurse was a herbivore. Thus, they occupied different ecological niches and hence were found in abundance in the same water body.